Quality of life following surgery for recurrent fistula-inano. - Seneviratne, S.A.; Samarasekera, D.N.; Kotalawala, W. (My University, 2009)
BACKGROUND: The management of fistula-in-ano remains a major surgical challenge and carries a significant morbidity affecting the quality of life (QOL) due to the disease and repeated operations. The aim of the study was to assess the QOL before and after successful surgical treatment of recurrent fistula-in-ano using the gastrointestinal quality of life index (GIQLI) which is a validated instrument consisting of 36 questions for measuring quality of life in patients with gastrointestinal disorders including fistula-in-ano. METHODS: All patients who underwent successful surgical treatment for recurrent fistula-in-ano over a period of 12 months were prospectively analysed using the GIQLI preoperatively and after a minimum of 18 months (mean, 24; range, 18-30) after complete cure following surgery. The difference in the QOL scores were analysed using Wilcoxon rank test. RESULTS: In the 21 patients recruited for the study there was a significant (P < 0.01) difference between the average preoperative (97.02) and postoperative (116.14) GIQLI scores. Of all the areas assessed by the GIQLI questionnaire, greater statistical significance was seen in areas of emotions (P < 0.01), social integration (P < 0.01) and effects of treatment (P < 0.01). CONCLUSIONS: Recurrent fistula-in-ano significantly affects the patients' QOL, and also, successful surgery results in significantly improved long-term QOL. This improvement shows the need for those patients with fistula-in-ano to be subjected to further surgery despite the possible risk of anal incontinence.